2014
DOI: 10.1002/pbc.25067
|View full text |Cite
|
Sign up to set email alerts
|

Malignant transformation of infantile hemangioma to angiosarcoma: Response to chemotherapy with bevacizumab

Abstract: We describe a child initially diagnosed with multi-focal infantile hemangioma (cutaneous, hepatic, pulmonary), a benign vascular lesion, which underwent malignant transformation to angiosarcoma. The use of anti-angiogenic agents, such as bevacizumab, an anti-vascular endothelial growth factor (VEGF) antibody, has been reported in adults with angiosarcoma. Treatment with chemotherapy (gemcitabine and docetaxel) and bevacizumab resulted in disease response with progression free survival of 12 months. This report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 20 publications
1
28
0
Order By: Relevance
“…Therefore, our data favor the possibility that early lymphatic vascular malformations can progress to cutaneous lymphangiosarcomas. Similar progressions have been seen in some clinical observations (Jeng et al, 2014; Quarmyne et al, 2012; Rossi and Fletcher, 2002). …”
Section: Discussionsupporting
confidence: 88%
“…Therefore, our data favor the possibility that early lymphatic vascular malformations can progress to cutaneous lymphangiosarcomas. Similar progressions have been seen in some clinical observations (Jeng et al, 2014; Quarmyne et al, 2012; Rossi and Fletcher, 2002). …”
Section: Discussionsupporting
confidence: 88%
“…A phase II trial concluded that bevacizumab is an effective and well-tolerated single-agent treatment for metastatic or locally advanced angiosarcoma (20). Several case reports demonstrated that combination therapy with bevacizumab and chemotherapy or radiotherapy may improve quality of life and survival in patients with metastatic angiosarcoma (21)(22)(23)(24)(25). In addition, another VEGF inhibitor, pazopanib, may prolong the PFS of metastatic non-adipocytic soft-tissue sarcoma after previous chemotherapy (26), particularly when used as maintenance therapy for PCA (16).…”
Section: Discussionmentioning
confidence: 99%
“…Similar transformation from vascular malformations to malignant vascular tumors have been seen in some clinical observations. 4,5 Our data indicate that sustained hyper-activation of mTORC1 signaling is necessary for the vascular tumor growth and maintenance in the mouse model. Rapamycin, a potent mTORC1 inhibitor, effectively leads to the regression of established tumors in the mutant mice.…”
mentioning
confidence: 95%